Algorithm of surgical treatment of complicated forms of chronic pancreatitis. - O. E. Kanikovskyi; I. V. Pavlyk; I. V. Oliinyk (Medičnì Perspektivi)
The purpose of the work was to evaluate the algorithm of surgical treatment of complicated forms of chronic pancreatitis. The results of surgical treatment of 181 patients with complicated forms of chronic pancreatitis were analyzed. 24.5% of patients were admitted with type B pain syndrome. Among them, all patients had multiple strictures of the main pancreatic duct and tissue pressure resistance was >200 mm Hg. Histologically,these patients had stage 4 of pancreatic fibrosis. A combined local resection by Frey-Izbickiy allows to reduce the number of relapses of pancreatic hypertension by 11.1%.